Comprehension students of dependence of an individual state of health from factors of a social medium. - Hotienko S.V; Azanova T.D (Kharkov National Pedagogical University, 2010)
Dependence of individual health of the student on factors of the modern life is construed. 600 students have taken part in research. The individual comprehension is made out by students of state of the health. Factors of social life which put the greatest harm segregated and hoist a state of health of youth. It is established, that as of today very sharply there is a problem with smoking and the use of alcohol. It is established, that the majority of students know what there should be a way of life for improving and maintainings of the health. It is revealed grievances of students to loads on exercises on physical training.